Synonymous and Biased Codon Usage by MERS CoV Papain-Like and 3CL-Proteases - Kandeel, Mahmoud; Altaher, Abdallah (Biological & pharmaceutical bulletin, 2017)
Middle East respiratory syndrome coronavirus (MERS CoV) is a recently evolved fatal respiratory disease that poses a concern for a global epidemic. MERS CoV encodes 2 proteases, 3C-like protease (3CLpro) and papain-like protease (PLpro). These proteases share in processing MERS CoV polyproteins at different sites to yield 16 nonstructural proteins. In this work, we provide evidence that MERS CoV 3CLpro and PLpro are subject to different genetic and evolutionary influences that shape the protein sequence, codon usage pattern, and codon usage bias. Compositional bias is present in both proteins due to a preference for AT nucleotides. Thymidine (T) was highly preferred at the third position of codons, preferred and overrepresented codons in PLpro, but was replaced by guanosine (G) in 3CLpro. Compositional constraints were important in PLpro but not in 3CLpro. Directed mutation pressure seems to have a strong influence on 3CLpro codon usage, which is more than 30-fold higher than that in PLpro. Translational selection was evident with PLpro but not with 3CLpro. Both proteins are less immunogenic by showing low CpG frequencies. Correspondence analysis reveals the presence of 3 genetic clusters based on codon usage in PLpro and 3CLpro. Every protein had one common cluster and 2 different clusters. As revealed by correspondence analysis, the number of influences on codon usage are restricted in MERS CoV 3CLpro. In contrast, PLpro is controlled by a broader range of compositional, mutational, and other influences. This may be due to the multifunctional protease, deubiquitination, and innate immunity suppressing profiles of PLpro.